The Role of Crystal Accumulation and Cumulate Remobilization in the Formation of Large Zoned Ignimbrites: Insights From the Aso-4 Caldera-forming Eruption, Kyushu, Japan - Keller, Franziska; Bachmann, Olivier; Geshi, Nobuo; Miyakawa, Ayumu (Frontiers in Earth Science, 2021)
The Aso-4 caldera-forming event (86.4 ±1.1 ka, VEI-8) is the second largest volcanic eruption Earth experienced in the past 100 ka. The ignimbrite sheets produced during this event are some of the first ever described compositionally zoned pyroclastic flow deposits exhibiting clear compositional, mineralogical and thermal gradients with stratigraphic position. Large quantities of the deposits are composed of crystal-poor, highly evolved juvenile pumices, while late-erupted pyroclastic flows are in many cases dominated by crystal-rich and less silicic scoriae. These petrological gradients in the Aso-4 deposits have been linked to extensive magma mixing of two compositionally distinct magmas in a complex upper crustal reservoir. However, new studies on several other zoned ignimbrites suggest that magma mixing alone is not sufficient to fully explain such strong zonations. Compositional gradients are expected to be dominantly caused by the recharge-induced reactivation of extracted melt pockets and their complementary cumulate leftovers in the upper crust. Here, we investigate bulk rock and matrix glass data together with detailed analysis of mineral chemistry in order to re-evaluate the Aso-4 deposits in light of these latest developments. Reverse chemical zoning in phenocrysts, Sr enrichment in euhedral rims of plagioclases and the presence of mafic minerals (clinopyroxene, olivine) indicate recharge of hot, mafic magmas shortly prior to eruption, inducing a mixing signature. However, the marked enrichment in some elements in bulk-rock analyses and the presence of highly evolved minerals (some in the form of glomerocrysts) in the late-erupted, crystal-rich units, provide clear evidence for crystal accumulation in these scoria. Mass balance modelling of P2O5, Sr and SiO2 supports the extraction of melt-rich lenses within an upper crustal mush zone, leaving a partly cumulative crystal residue. We therefore propose an origin of the compositionally zoned Aso-4 ignimbrite largely by erupting a heterogeneous upper crustal reservoir, consisting of crystal-poor rhyodacitic melt pockets within a cumulate mush. This complex reservoir was reactivated by mafic recharge shortly prior to eruption, imparting an additional mixing signature to the deposits.